Migration of Workers and Persons and the Integration Processes in the Polish Labour Market with Respect to Poland’s Membership in the European Union - Wysokińska, Zofia (Comparative Economic Research. Central and Eastern Europe, 2006)
This study attempts to present migration trends in Poland against the backdrop of integration processes occurring in the labour market in the context of Poland’s membership in the European Union. The chapter consists of 3 parts: • presentation of the limited access of Polish labour workforce to the EU labour market within the Europe Agreement and Accession Treaty, • presentation of recommendations of the European Commission for the candidate countries’ adjustments in the following areas: co-ordination of the social security systems, equal treatment of men and women, occupational health and safety, some aspects of the labour law. • presentation of some trends of migration (immigration and emigration ) into and from Poland during the transition period.